THE USE OF OUTDOOR-BASED LEARNING STRATEGY TO IMPROVE THE STUDENTS’ SPEAKING SKILL IN SMP UNISMUH MAKASSAR - Nur Asti, Nur Asti; Rum, Eka Prabawati; AM, St. Asmayanti (FKIP Unismuh Makassar, 2025)
This research aimed to find out whether or not the use of Outdoor-Based Learning Strategy can improve the students speaking skill in terms of fluency and accuracy. This research was conducted in SMP Unismuh Makassar by using the true experimental design through two groups of experimental class and controlled class, and collected the data by giving pre-test, treatment, and post-test. The population of this research was the first grade students at SMP Unismuh Makassar. The sample was taken by using purposive sampling technique which consisted with 17 students as experimental class and 17 students as controlled class. The research findings showed that the first grade students of SMP Unismuh Makassar have a significant different between students’ post-test in experimental class and controlled in speaking fluency and accuracy. The mean score of post-test (2.41) in experimental class was higher than the mean score of post-test (1.94) in controlled class. While in Speaking accuracy the mean score of post-test (1.94) in experimental class as higher than the mean score post-test (1.65) in controlled class. From t-test the t-test value in speaking fluency is 4.315 > 0.05 and in speaking accuracy 3.395 > 0.05. which mean that there is significant difference between before and after giving the treatment. It indicated that the null hypothesis (HI) was accepted, and the null hypothesis (H0) was rejected. It shows that the use of outdoor-based learning significantly improve the students’ speaking fluency and accuracy.